COMPARISON BETWEEN ON MALAYSIA AIRLINES SYSTEM (MAS) AND AIRASIA - Ariffin, IA; Yajid, Mohd Shukri Ab; Johar; MGM (International Journal of Psychosocial Rehabilitation, 2020)
This investigation having the prime aim to have the comparison between Malaysia Airlines System (MAS), and Air Asia. The comparison was done in the context of consumer. There was survey conducted on the individuals who exercised the both airlines. The data was analyzed by employing the Statistical Package of Social Sciences (SPSS). These tools include descriptive analysis, one independent t-test and Chi Square test. There were mixed results from the study.